Controlled Hypotension During Functional Endoscopic Sinus Surgery (FESS) - A Comparative Evaluation Between Esmolol and Nitroglycerine - Gowtham, Kotaru; Shankar, Mittapally; Sowjanya, Bhagothula (Faculty of Medicine, Brawijaya University, 2023)
Background: Intraoperative bleeding is a frequent complication in functional endoscopic sinus surgery (FESS). Controlled hypotension is a useful technique for enhancing the surgical field and reducing operative blood loss. Nitrovasodilators and beta receptor antagonists are effective options for regulated hypotensive anaesthesia during FESS. We assessed the efficacy of esmolol and nitroglycerine for controlled hypotension in subjects undergoing FESS.Methods: A source of 64 participants undergoing elective FESS, were randomly allocated to group N (n=32), which got an intravenous Nitroglycerin infusion at 5–10 µg/kg/min, and group E (n=32), which received an initial bolus of 500 mcg/kg of intravenous esmolol over 30 seconds. Hemodynamic parameters were measured and the visibility of the surgical field was assessed using the average category scale (ACS).Result: In groups N and E, the mean surgical duration was 113.5 minutes and 102.34 minutes, respectively, and the mean operative blood loss was 188.5 ml and 173.7 ml. The esmolol group experienced a rapid decline in heart rate, and there was a statistically significant difference in mean SBP, DBP, and MAP across the study groups. At the 10-min, the majority of cases displayed scores of 3 in group E and 4 in group N. In the esmolol group, there was a significant difference between the hypotensive phase and the hemodynamic measures (p<0.05).Conclusion: Nitroglycerine and esmolol were effective in controlling hypotension. However, esmolol was superior in controlling the operative bleeding, surgical duration, enhanced surgical field visibility, and absence of reflex tachycardia compared to nitroglycerine